Urban subsurface drainage as an alternative water source in a drying climate. Issue 2 (2nd July 2016) - Davies, Carl G.; Vogwill, Ryan; Oldham, Carolyn
Abstract: The Swan Coastal Plain in Western Australia has been undergoing rapid urban growth and with it comes two primary water related concerns. The first is the spread of development into areas with shallow water tables which requires costly water management to control groundwater level rise; the second is the limited groundwater allocation available in areas earmarked for development. In regard to the second, a potential water source for developments on low-lying land is subsurface drainage that has been installed to control groundwater levels. This research project is being undertaken at two urban developments on low-lying land and includes subsurface drain flow and quality monitoring. The field data will inform numerical hydrogeological and hydrogeochemical models. The objective is to quantify the subsurface drainage volume available as a water resource, and the environmental and operational risk of utilising the resource. The results to date show potential for diverting subsurface flow for direct irrigation in the drier months without the requirement for wet season storage and dry season reuse. Annual subsurface drainage flows provide multiple times the annual irrigation demand if wet season flows are stored and reused by aquifer storage and recovery, and provides opportunity for beneficial use of excess water.